1. The problem statement, all variables and given/known data Solve this differential equation: (y^2 +1)*dx + (2xy + 1)*dy = 0 2. Relevant equations dy/dx + P(x)*y = Q(x) u(x) = e^(integral of P(x)dx) (d/dx)(u(x)*y) = Q(x)*u(x) y = (integral of (Q(x)*u(x)dx))/(u(x) 3. The attempt at a solution I tried dividing by dx then distributing and rearranging to get it into the right form, but run into problems: y^2 + 1 + 2xy*dy/dx + dy/dx = 0 dy/dx + y/2x = (-1/(2xy))(dy/dx) -1/(2xy) this is the closest I could get it to the right form. It would give me u(x) = x^(1/2), but I wouldn't be able to integrate the right side as it would have both x and y. Is there a way to get past this, or did I just rearrange poorly? I just integrated it anyway and the part that was integrated with respect to x I held y as constant, and vice versa, but I'm sure it's wrong so I won't show how I did that. This is for a calc II class so it should be doable without any advanced tricks. thanks!